Study of variation in natural frequencies of bio-composites due to structural damage. (1st October 2020) - Shah, Aarsh J.; Pandya, Tejas S.; Street, Jason
ABSTRACT: The purpose here is to study the variation in the natural frequency of a material due to damage. Also, compare the shift in Natural Frequency that of a SYP-SP (Sweet Potato) bio-composite to a commercial SYP composite. Additionally, the motivation behind the study is to eventually provide biodegradable materials, as petroleum-based products being a finite resource and having more potential to harm the environment. The researcher obtained the Natural Frequencies by Experimental modal analysis using a cantilever beam vibration technique. The shift for the first three natural frequencies for damage induced SYP-SP composite was 10%, 8.6%, and 9.5% and for SYP-Commercial composite was 7.95%, 0.7%, and 0.9% respectively. The undamaged specimens of SYP-SP bio-composite and that of a commercial SYP composite showed behaviour almost on similar lines. Thus, stating the potential use of SYP-SP bio-composite for commercial applications like wood flooring, fencing, and other related applications.